Women’s empowerment and fertility: A review of the literature - Upadhyay, Ushma D. (2014)
Women’s empowerment has become a focal point for development efforts worldwide and there is a need for an updated, critical assessment of the existing evidence on women’s empowerment and fertility. We conducted a literature review on studies examining the relationships between women’s empowerment and several fertility-related topics. Among the 60 studies identified for this review, the majority were conducted in South Asia (n = 35) and used household decision-making as a measure of empowerment (n = 37). Overall, the vast majority of studies found some positive associations between women’s empowerment and lower fertility, longer birth intervals, and lower rates of unintended pregnancy, but there was some variation in results. In many studies, results differed based on the measure of empowerment used, sociopolitical or gender environment, or sub-population studied. This article is one of the first evaluations of the literature assessing the relationships between women’s empowerment and fertility. We identify several key issues that merit further investigation.